Factors Affecting The Choices of Healthy Diet among Adolescents in Rural Areas - Dewanti, Ritma; Probandari, Ari; Mulyani, Sri (Universitas Airlangga, 2022)
Many adolescents tend to pick unhealthy diets with high amount of sugar, salt and fat, while the number of adolescents who consume vegetables and fruit is relatively low. As adolescents begin to pick their own diets by themselves, there are certain reasons behind each of their preferences in foods. This study was aimed to analyze the factors affecting the choices of healthy diet among adolescents in rural areas. This was quantitative research with analytical and observational research method with a cross sectional design. The data sampling method used in this study was a multistage random sampling method. This research was conducted to 160 respondents with a population of 1,143 from 10 different high schools. The sample size was calculated using the OpenEpi software. The data on factors or reasons behind the choice of healthy diet was taken using the Food Choice Questionnaire (FCQ), while the data on the choices of healthy foods was taken using a structured questionnaire, both of which had been tested for validity and reliability. The collected data were analyzed using the Spearman Rank test. The main reasons that can influence adolescents to pick healthy diets in rural area were for healthiness concerns, the natural contents of the foods, and body weight control (BW) (p=<0.005). It is recommended for adolescents to optimize their knowledge and skills in food selection, especially healthy food.